Leadership and Motivation as Determinants of Teacher Performance: Evidence from Indonesian Junior Secondary Schools - Zulfiter, Zulfiter; Fitria , Happy; Nurkhalis, Nurkhalis (Yayasan Darussalam Bengkulu, 2023)
Improving teacher performance has become a central concern in educational research, as teacher effectiveness is strongly linked to student achievement and the overall quality of schooling. This study aimed to investigate the influence of principals’ leadership style and teachers’ work motivation on teacher performance in junior secondary schools in Sungai Rotan District, Indonesia. Employing a quantitative correlational design, data were collected from 98 teachers using a structured questionnaire that measured leadership style, work motivation, and teacher performance, with validity and reliability established through expert review, factor analysis, and Cronbach’s alpha. Data analysis was conducted using multiple linear regression with SPSS. The results indicated that both leadership style and work motivation had significant positive effects on teacher performance, with work motivation showing a stronger influence, while the combined model explained 34.3% of the variance in teacher performance. The discussion suggests that principals who demonstrate supportive leadership practices can enhance teachers’ intrinsic and extrinsic motivation, which in turn improves their instructional planning, classroom management, and professional responsibility. This study contributes novelty by examining the simultaneous influence of leadership and motivation in the Indonesian junior secondary school context, a relationship that has been underexplored in prior research. The findings imply that effective leadership development and motivational support are essential strategies for policymakers and educational practitioners seeking to improve teacher performance and strengthen school effectiveness in developing country contexts.